Construction of a diphtheria toxin A fragment-C180 peptide fusion protein which elicits a neutralizing antibody response against diphtheria toxin and pertussis toxin. - Barbieri, J T (1992)
A genetically engineered gene fusion was constructed which encoded a nontoxic derivative of the A fragment of diphtheria toxin joined to the C180 peptide of the S1 subunit of pertussis toxin. The product of this gene fusion, termed the DTA-C180 protein, was purified from the periplasm of Escherichia coli to approximately 80% purity. The DTA-C180 protein possessed an apparent molecular weight of 43,000 by reduced sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The DTA-C180 protein was cleaved into two tryptic peptides, which migrated with apparent molecular weights of approximately 22,000. One tryptic peptide reacted with diphtheria antitoxin, while the other tryptic peptide reacted with anti-C180 peptide immunoglobulin G. The DTA-C180 protein did not inhibit protein synthesis or stimulate clustering morphology in Chinese hamster ovary cells. The DTA-C180 protein elicited an immune response, in guinea pigs, against both the DTA and C180 peptide components of the fusion protein, with alum being a more efficient adjuvant than Freund's adjuvant for eliciting neutralization titers. Neutralization titers elicited by DTA-C180 protein were weaker than those elicited by diphtheria toxoid and pertussis toxin 9K/129G, a genetically engineered double mutant of pertussis toxin. Three doses of DTA-C180 protein yielded a neutralization titer of 1/750 against pertussis toxin in Chinese hamster ovary cells and a neutralization titer of 1/50 against diphtheria toxin in Vero cells. This is the first report of a protein derived from a recombinant S1 subunit that elicits a neutralizing titer against pertussis toxin.